Cohesiveness as a Symbolic Power of Mobile Legends Online Game Community - Rahmatiah Rahmatiah; Dondick Wicaksono Wiroto; Nurhayati Husain; Hapsawati Taan; Abdul Malik Iskandar (Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Online games played in groups require cohesiveness and effective coordination among team members for successful cooperation. The sociological study of cohesiveness remains neces- sary because the analysis of interactions found in number of studies has not been sufficient- ly in-depth. These studies have failed to reveal the social significance of the term “cohesiveness” or the importance of good coordination as a symbolic force within a group. Several Mobile Legends players in Gorontalo are part of a community renowned for their remarkable reputation in winning matches worldwide. This success has led to the expansion of the group into 3 squads (sparring groups). This research aims to explore how community cohesiveness can serve as a symbolic force, employing qualitative methods with a narrative approach to provide detailed analysis. As a symbolic force, cohesiveness develops through three processes: the initial emergence of cohesiveness, its progression towards community superiority, and finally how the community maintains its cohesion. The symbolic power of community cohesiveness encompasses role symbols and attitude symbols among its members.